Pengaruh Tingkat Pengetahuan Gizi Seimbang dengan Kejadian Overweight - Muhammad Rizki Maulana; Nuzirwan Acang; Mia Yasmina (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. Nutritional problems are one of the unresolved problems in Indonesia, one of which is excess nutrition which can cause overweight which is often found. Based on research on basic health data in 2013, there has been an increase in the prevalence of overweight since 2010 finding 1.4% until 2013 to 7.3%. Nutritional knowledge of a person or individual is an important factor in a person's nutritional status. This research is an analytic observational study with a cross sectional design method. The research sample was taken using a probability sampling technique with a simple random sampling type, amounting to 228 respondents and the respondents were selected using a lottery method so that there were 95 respondents. The research data was taken from primary data resulting from filling out the Google form which contained a General nutritional knowledge questionnaire with a total of 13 questions and data on height and weight that had been measured for first year students in a place, namely in the UNISBA Faculty of Medicine Building. The results obtained based on the data obtained using the chi-square test obtained a value of p = 0.075 (p> 0.05), which means there is no relationship between the level of knowledge about balanced nutrition and the incidence of overweight in UNISBA Medical Faculty students. In conclusion, there is no relationship between the level of knowledge of balanced nutrition and the incidence of overweight in FK UNISBA level one students. Abstrak. Permasalahan gizi merupakan salah satu masalah yang belum selesai di Indonesia, salah satunya adalah kelebihan gizi yang dapat menimbulkan overweight yang banyak dijumpai. Berdasarkan riset data kesehatan dasar 2013, terjadi peningkatan pada prevalensi overweight sejak 2010 mendapati 1,4% hingga tahun 2013 menjadi sebesar 7,3%. Pengetahuan gizi pada seseorang atau individu merupakan salah satu faktor penting dalam status gizi seseorang. Penelitian ini merupakan penelitian observasional analitik dengan metode desain cross sectional. Pengambilan sampel penelitian menggunakan teknik probability sampling dengan jenis simple random sampling yang berjumlah 228 responden dan dilakukan pemilihan responden menggunakan metode undian sehingga terdapat 95 responden. Data penelitian diambil dari data primer hasil dari pengisian google form yang berisikan General nutritional knowledge questionnaire dengan jumlah 13 pertanyaan dan data dari tinggi badan serta berat badan yang sudah diukur kepada mahasiswa tingkat satu di tempat, yaitu di Gedung Fakultas Kedokteran UNISBA. Hasil penelitian yang didapatkan berdasarkan data yang didapat dengan menggunakan uji chi-square didapatkan nilai p= 0.075 (p>0,05) yang berarti tidak terdapat hubungan antara tingkat pengetahuan tentang gizi seimbang dengan kejadian overweight pada mahasiswa Fakultas Kedokteran UNISBA. Simpulan, tidak terdapat hubungan antara tingkat pengetahuan gizi seimbang dan kejadian overweight pada mahasiswa FK UNISBA tingkat satu.